2007
DOI: 10.1161/01.res.0000261924.76669.36
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of Autophagy in the Heart During Ischemia and Reperfusion

Abstract: Abstract-Autophagy is an intracellular bulk degradation process for proteins and organelles. In the heart, autophagy is stimulated by myocardial ischemia. However, the causative role of autophagy in the survival of cardiac myocytes and the underlying signaling mechanisms are poorly understood. Glucose deprivation (GD), which mimics myocardial ischemia, induces autophagy in cultured cardiac myocytes. Survival of cardiac myocytes was decreased by 3-methyladenine, an inhibitor of autophagy, suggesting that autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

43
970
6
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,351 publications
(1,020 citation statements)
references
References 32 publications
43
970
6
1
Order By: Relevance
“…However, stimulated autophagy has been implicated in several types of cardiomyopathy 25. Autophagy is anti‐apoptotic and contributes to cellular recovery during brief myocardial ischaemia, but the subsequent reperfusion could cause excessive autophagy, which is considered cytotoxic and termed as class II programmed or autophagic cell death 6, 7, 8, 26. Our previous studies showed that inhibiting excessive autophagy could significantly decrease the infarct size and improve cardiac function after I/R‐induced myocardial injury 27, 28.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, stimulated autophagy has been implicated in several types of cardiomyopathy 25. Autophagy is anti‐apoptotic and contributes to cellular recovery during brief myocardial ischaemia, but the subsequent reperfusion could cause excessive autophagy, which is considered cytotoxic and termed as class II programmed or autophagic cell death 6, 7, 8, 26. Our previous studies showed that inhibiting excessive autophagy could significantly decrease the infarct size and improve cardiac function after I/R‐induced myocardial injury 27, 28.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced levels of autophagy have been observed in the heart during both ischaemia and reperfusion 4, 5, 6. Studies have reported that autophagy has a dual, opposite role in the heart, depending on the stimulus 7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence indicates that AMPK can be activated by metformin in the brain, exerting a neuroprotective role in response to energy depletion through maintaining cellular energy homeostasis,24, 25, 26 promoting mitochondrial biogenesis,27 and increasing brain‐derived neurotrophic factor expression to promote neuronal survival 28. Recently, autophagy has been proposed as a downstream target of AMPK, and AMPK‐induced autophagy activation protects against ischemic injury to peripheral tissue injury29, 30, 31 as well as ischemic brain injury 32. These studies have prompted us to hypothesize that metformin pretreatment may prime the brain to better stand ischemic damage resulting from asphyxial CA and cardiopulmonary resuscitation (CA/CPR) through promoting AMPK‐mediated autophagy activation.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments in mammals have demonstrated that AMPK controls autophagy through mammalian target of rapamycin (mTOR) and Atg1/ULK1 signalings, which augments the quality of cellular housekeeping (Alers et al ., 2012). Previous studies indicate that the activation of AMPK is able to induce autophagy and subsequently confer to the protective effects against ischemic injury in the heart (Matsui et al ., 2007), kidney (Wang et al ., 2013), liver (Zaouali et al ., 2013), and muscular tissues (Pauly et al ., 2012). In the present study, we investigated the effects of β‐GPA in dietary supplements on lifespan of Drosophila and the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%